Pengaruh Sosialisasi Pajak, Penerapan PP No 46 Tahun 2013 dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak Badan Umkm di Sidoarjo - Shinta Octavianingrum, Dwi (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2019)
This journal aims to determine the effect of tax socialization, the application of PP No. 46 of 2013 and tax sanctions on tax compliance of MSME corporate bodies in Sidoarjo both partially and simultaneously. This study also aims to find out which independent variable most influences the dependent variable, namely tax compliance of MSME agencies in Sidoarjo. The research method used in this study is a quantitative approach. The sample used amounted to 100 obtained using the Slovin formula. The technique used in sampling is by the NonProbability Sampling technique. Data collection is done by distributing questionnaires. Data were analyzed using IBM SPSS Statistics 24 with multiple linear regression analysis techniques. The results of the study showed that tax socialization and tax sanctions significantly affected the taxpayer compliance of SMEs in Sidoarjo. While the application of PP No. 46 of 2013 does not partially affect the dependent variable. However, simultaneous third independent variables significantly influence taxpayer compliance